2017
DOI: 10.1299/jamdsm.2017jamdsm0083
|View full text |Cite
|
Sign up to set email alerts
|

Different teeth profile shapes of polymer gears and comparison of their performance

Abstract: This article presents a lifespan testing analysis of polymer gears manufactured by cutting. Compared to injection molding, machine cutting provides higher accuracy of gear geometry. Two different tooth flank geometries were tested; i.e. involute and S-gears. In theory, S-gears have several advantages over involute gears due to the convex/concave contact between the matching flanks. The theoretical tooth flank geometry of S-gears provides more rolling and less sliding between the matching flanks, compared to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Previous research showed a clear distinction between Sand E-gear geometry in favour of former, which can be attributed to already mentioned attributes of S-gears [2][3][4][5]. Two types of experiments were conducted: a) durability tests where gears made of POM (driving) and PA66 (driven) run up to failure and tests where both gears were made of POM; b) long term tests up to about 20 million cycles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research showed a clear distinction between Sand E-gear geometry in favour of former, which can be attributed to already mentioned attributes of S-gears [2][3][4][5]. Two types of experiments were conducted: a) durability tests where gears made of POM (driving) and PA66 (driven) run up to failure and tests where both gears were made of POM; b) long term tests up to about 20 million cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Tests are summarized in Fig. 7 [4] are presented, with a far better durability. Gears are with the same geometry, experiments conducted on the basically the same machine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the contact load is lower [31].Tests were performed, which led to the confirmation of the assumption that the theoretical tooth flank geometry of S-gears provides more rolling and less sliding between the matching flanks compared to involute gears. The convex-concave contact leads to lower contact stress, which in combination with less sliding, means lower losses due to sliding friction, and consequently, less heat generated [32].The S-gears were also used by the design of the planocentric gear boxes and devices for large transmission ratios, primarily applied in automation and mechatronic industry, which decrease rotational movement and increase torque to the largest possible extent in the smallest available space [33].In all applications where the reduction gear must be as small as possible, a planetary gearset is preferred as it has the additional advantage of the input and output shafts being coaxial. The Wolfrom gear is suitable for high speed ratios, and has an efficiency that is not optimal but still acceptable.…”
mentioning
confidence: 99%
“…Tests were performed, which led to the confirmation of the assumption that the theoretical tooth flank geometry of S-gears provides more rolling and less sliding between the matching flanks compared to involute gears. The convex-concave contact leads to lower contact stress, which in combination with less sliding, means lower losses due to sliding friction, and consequently, less heat generated [32].…”
mentioning
confidence: 99%